(untitled) (Proceedings of Southern Federal University. Philology, 2012)
Andreeva O.S. Keywords: Mayakovsky, genre, epos, lyrics, drama, menippea, dialogical paradigm, syncretic genre. The analysis presented in the article is based on M.M. Bakhtin’s theory of the dialogical nature of artistic expression. The detailed analysis of the prologue to the poem and the final part of «Poslednee» defines the basic strategy of the fiction analysis from the point of view of its genre nature. Moreover, it determines the nature of the trinitarian form of the poem «Chelovek» (“The Man”) which combines the genres of epos, lyrics and drama. >Three sisters. Natasha is viewed as a bearer of the urban petty bourgeois culture at the turn of the 20th century.